Vulva Hygiene Dalam Pencegahan Keputihan Di SMA Al-Amjad Medan - Nurrahmaton, Nurrahmaton; Juliani, Sri (Universitas Malahayati Bandar Lampung, 2021)
Background: Leucorrhoea is one of the reproductive health experienced by young women. Many teenagers do not know about vaginal discharge, vaginal discharge occurs due to poor hygiene practices, to improve the knowledge and attitudes of young women, for this chance the students is tought about health education about vulva hygiene in the prevention of vaginal discharge. Objective: This study aims to find out the effect of health education on vulva hygiene on the knowledge and attitudes of young women in the prevention of vaginal discharge in SMA Al-Amjad. Method: This research is a quantitative study that used pre-experimental design with one group pre-test and pot-test design approach. Data was collected by using a questionnaire. The sample of this study were female teenagers of SMAAl-Amjad which were obtained through 85 stratified random sampling. Data analysis used the Wilcoxon signed rank test. Results: The showed that the knowledge of young women before being given health education had an average value of 53.85, an increase to 82.06 after being given health education. The same results showed the attitude of young women before being given health education with an average value of 68.24 an increase to 77.05 after being given health education. Statistical test results obtained p value = .000 (<.05). Conclusion: of this study is the influence of health education on vulva hygiene on the knowledge and attitudes of young women in the prevention of vaginal discharge. SuggestionThis counseling will help adolescents obtain information and increase their knowledge about reproductive health. Keywords: Health Education, Leucorrhoea, Knowledge, Youth, Attitude, Vulva Hygiene ABSTRAK Latar Belakang : Keputihan adalah salah satu kesehatan reproduksi yang dialami remaja wanita. Banyak remaja tidak mengetahui tentang keputihan. Keputihanterjadi dikarenakan praktik hygiene yang buruk. Keputihan normal tidak memerlukan pengobatan khusus dan akan membaik dengan sendirinya dengan hygiene yang benar. Namun, bila ternyata yang dialami adalah keputihan yang tidak normal, dapatberpotensi mengganggu fungsi organ kewanitaan dan mengancam kesuburan para remaja saat mereka dewasa nanti.Tujuan: Penelitian ini bertujuan untuk melihat pengaruh health education tentang vulva hygiene terhadap pengetahuan dan sikap remaja putri dalam pencegahan keputihan di SMA Al-Amjad. Metode: Penelitian ini merupakan penelitian kuantitatif menggunakan design pre-eksperimental dengan pendekatan one group pre-test pot-test design. Data dikumpulkan menggunakan kuesioner. Sampel penelitian ini adalah remaja putri SMA Al-Amjad yang diperoleh melaui stratified random sampling berjumlah 85 orang. Analisis data menggunakan uji wilcoxon signed rank test. Hasil: penelitian menunjukkan pengetahuan remaja putri sebelum diberikan pendidikan kesehatan memiliki nilai rata-rata 53,85 terjadi peningkatan menjadi 82,06 setelah diberikan pendidikan kesehatan. Hasil yang sama menunjukkan sikap remaja putri sebelum diberikan pendidikan kesehatan dengan nilai rata-rata 68,24 terjadi peningkatan menjadi 77,05 setelah diberikan pendidikan kesehatan. Hasil uji statistic didapatkan nilai p=0,000 (<0,05). Kesimpulan: Terdapat pengaruh health education tentang vulva hygiene terhadap pengetahuan dan sikap remaja putri dalam pencegahan keputihan. Saran Penyuluhan ini akan membantu remaja memperoleh informasi dan menambah wawasan mereka tentang kesehatan reproduksi. Kata Kunci : Health Education, Keputihan, Pengetahuan, Remaja, Sikap, Vulva Hygiene